2013
DOI: 10.7567/apex.6.045001
|View full text |Cite
|
Sign up to set email alerts
|

Selective-Area Growth of InAs Nanowires with Metal/Dielectric Composite Mask and Their Application to Vertical Surrounding-Gate Field-Effect Transistors

Abstract: We attempted the selective-area metalorganic vapor-phase epitaxial (SA-MOVPE) growth of InAs nanowires (NWs) using a tungsten/dielectric composite mask and fabricated nanowire vertical surrounding-gate field-effect transistors (NW-VSG-FETs), where tungsten served as both the mask in SA-MOVPE growth and the bottom electrode of the FET. The growth of NWs with diameters as low as 100 nm was demonstrated using the composite mask. The fabricated NW-VSG-FET exhibited improved drain current density as compared with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…[9][10][11][12] The integration of such vertical semiconducting NWs to semiconducting substrates is currently of great interest because it shows tremendous potential in the creation of next-generation electronic, photonic, spintronic, and biochemical sensing devices in nanometer scale. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Among such a large number of device applications using vertical NWs, we have investigated the device characteristics of NW FETs using our III-V compound semiconducting NWs [25] in the horizontal [27] and vertical [28,29] configurations, and the magnetotransport properties of the semiconducting NWs. [30] While we have investigated the magnetotransport properties as well in ferromagnet/semiconductor hybrid NWs and nanostructures as a short-term aim, [31][32][33] as a promising technological combination between conventional spintronic devices [1,2] and our semiconducting NW technologies [25,[27][28][29][30]33] for future development of semiconductor industry, the long-term objective of our studies is to create vertical NW spin FETs and MOSFETs using semiconducting NWs with suitable ferromagnetic electrode materials, such as CoFe and CoFeB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] The integration of such vertical semiconducting NWs to semiconducting substrates is currently of great interest because it shows tremendous potential in the creation of next-generation electronic, photonic, spintronic, and biochemical sensing devices in nanometer scale. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] Among such a large number of device applications using vertical NWs, we have investigated the device characteristics of NW FETs using our III-V compound semiconducting NWs [25] in the horizontal [27] and vertical [28,29] configurations, and the magnetotransport properties of the semiconducting NWs. [30] While we have investigated the magnetotransport properties as well in ferromagnet/semiconductor hybrid NWs and nanostructures as a short-term aim, [31][32][33] as a promising technological combination between conventional spintronic devices [1,2] and our semiconducting NW technologies [25,[27][28][29][30]33] for future development of semiconductor industry, the long-term objective of our studies is to create vertical NW spin FETs and MOSFETs using semiconducting NWs with suitable ferromagnetic electrode materials, such as CoFe and CoFeB.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Among such a large number of device applications using vertical NWs, we have investigated the device characteristics of NW FETs using our III-V compound semiconducting NWs [25] in the horizontal [27] and vertical [28,29] configurations, and the magnetotransport properties of the semiconducting NWs. [30] While we have investigated the magnetotransport properties as well in ferromagnet/semiconductor hybrid NWs and nanostructures as a short-term aim, [31][32][33] as a promising technological combination between conventional spintronic devices [1,2] and our semiconducting NW technologies [25,[27][28][29][30]33] for future development of semiconductor industry, the long-term objective of our studies is to create vertical NW spin FETs and MOSFETs using semiconducting NWs with suitable ferromagnetic electrode materials, such as CoFe and CoFeB. [4][5][6][7][8] Therefore, for the creation of vertical NW spin transistors, it is indispensable to control the magnetic domain structures and magnetization DOI: 10.1002/pssb.202100519…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic decomposition of group-III precursors molecules on the Au droplet surface caused a faster growth of GaP, GaAs and InAs VLS NWs [48] while fast lateral growth in SAG was attributed to enhanced surface diffusion of group-III precursors on a W mask surface [49,50]. Growth selectivity in the latter process was found to significantly decrease for low growth temperature and rough metal surfaces [28,51]. We stress that in our work the smooth back face of an integrated TiN layer was exposed, the roughness of which was set by the native SiO 2 layer below (see Fig.…”
Section: Supporting Information Supporting Information 1: Hybrid-tase...mentioning
confidence: 96%
“…We also point out that the finite lamella thickness of ∼ 80 nm might cause the observed interface roughness to appear larger. In previous studies, the roughness of metal top surfaces was found to promote detrimental parasitic nucleation during semiconductor epitaxy [28]. In contrast, our approach utilizes the pristine and freshly exposed TiN back surface, which allows selective growth in geometries with high aspect ratio.…”
mentioning
confidence: 97%
“…We developed selective‐area metal‐organic vapor phase epitaxy (SA‐MOVPE) to demonstrate the bottom‐up formation of ferromagnetic MnAs NCs on semiconducting (111)B substrates to avoid possible problems caused by the statistical fluctuations. We used SA‐MOVPE because it enables us to control the size, shape, number, position, and spatial arrangement of not only the ferromagnetic MnAs NCs , but also the vertical free‐standing semiconducting NWs, which are promising building blocks for future nanoelectronics and photonics . NWs fabricated using the FM III–V hybrids or diluted magnetic semiconducting materials have recently been created using a conventional vapor‐liquid‐solid (VLS) method and thermal annealing after the deposition or ion beam implantation of the Mn nanoparticles onto the VLS‐grown NWs for nanospintronic device applications using NWs .…”
Section: Introductionmentioning
confidence: 99%